Measurements of Ground Temperature at Various Depths - Kalogirou, Soteris A.; Florides, Georgios A. (My University, 2004)
Information on ground temperatures is necessary for many construction projects. These include the calculations of heat losses of buildings to the ground and the design of thermal energy storage equipment. With the growing need for conservation of energy, information on ground temperature is also important for the possible use of the ground as a source for heat pump applications. Engineers and architects concerned with these problems require knowledge of the factors that determine ground temperatures as well as an understanding of how these temperatures vary with time and depth from the surface. The earth temperature beyond a depth of 1 meter is usually insensitive to the diurnal cycle of air temperature and solar radiation and the annual fluctuation of the earth temperature extends to a depth of 9 to 12 meters. This study discusses the factors affecting ground temperature and the winter temperature variation with depth. Temperatures were measured in Nicosia, Cyprus, with thermocouples inserted in the ground at a depth of 0m to 50m. It was found that the short-period temperature variations in winter, are prominent to a depth of approximately 0.5m. The temperature measurements are compared to the calculated values resulting from the use of the Kasuda formula adopted by the TRNSYS type 501, with the results showing good agreement within about 0.5°C for a depth greater than 2 meters.
Keywords: Ground temperature; Kasuda formula; TRNSYS